2014
DOI: 10.1063/1.4896117
|View full text |Cite
|
Sign up to set email alerts
|

Transmission line transformer for reliable and low-jitter triggering of a railgap switch

Abstract: The performance of railgap switch critically relies upon multichannel breakdown between the extended electrodes (rails) in order to ensure distributed current transfer along electrode length and to minimize the switch inductance. The initiation of several simultaneous arc channels along the switch length depends on the gap triggering technique and on the rate at which the electric field changes within the gap. This paper presents design, construction, and output characteristics of a coaxial cable based three-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…A reduction in t d and σ d can also be achieved through UV illumination of the discharge gap [12] and by applying a fast dV/dT trigger pulse [13]. Verma et al [14] experimentally studied the switching performance in j(SF 6 ): j(Ar) = 20:80 by applying a trigger pulse of slew rate ∼0.07 k V ns −1 , 6 kV ns −1 , and reported that by applying a trigger pulse with high dV/dT the t d and σ d were improved. (Where 'dV/dT' implies to rate of rise of trigger voltage with time (T)).…”
Section: Introductionmentioning
confidence: 99%
“…A reduction in t d and σ d can also be achieved through UV illumination of the discharge gap [12] and by applying a fast dV/dT trigger pulse [13]. Verma et al [14] experimentally studied the switching performance in j(SF 6 ): j(Ar) = 20:80 by applying a trigger pulse of slew rate ∼0.07 k V ns −1 , 6 kV ns −1 , and reported that by applying a trigger pulse with high dV/dT the t d and σ d were improved. (Where 'dV/dT' implies to rate of rise of trigger voltage with time (T)).…”
Section: Introductionmentioning
confidence: 99%